Pembelajaran Inovatif dalam Meningkatkan Keterampilan Berpikir Tingkat Tinggi dan Keterampilan Komunikasi: Tinjauan Sistematis - Adilah Afikah; Eli Rohaeti; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aimed to overview learning strategies to create learning innovation that can improve students' high-order thinking and communication skills in science learning. This research was classified as a systematic review. The data used in this study was secondary. This study's 15 secondary data sources consist of books, proceedings, and scientific articles in reputable journals. The data analysis using Miles & Huberman analysis technique. Data analysis includes data reduction, data presentation, and conclusion. The result of this study is that problem-based learning and inquiry-based instruction is learning strategies that can improve students' high-order thinking skills. The learning strategy that can improve students' communication skills is problem-based learning. High-order thinking skills and communication skills can influence each other. It was hoped that with this research, innovative learning centered on learning models and learning media could be developed so that students have high-order thinking and communication skills with good categories in future education.